(untitled) (Research, Society and Development, 2022)
The sorghum biomass is an important raw material in energy generation, presenting agronomic potential to compose the cultivation areas, providing raw material for energy generation industry, in this sense twenty-five genotypes of sorghum biomass were evaluated in an experiment conducted in the 2019/20 agricultural season in the months of November to May in the experimental area of the Laboratory of Genetic Resources & Biotechnology of the State University of Mato Grosso. A randomized block design with three repetitions was used and the experimental plots were composed of two rows of plants with 5.0 meters in length spaced 0.70 m apart. The evaluations were performed through samples of 10 plants per plot that occurred 180 days after sowing, evaluating five agronomic characteristics: flowering, plant height, cane diameter, green mass production and dry matter production. The hybrids that stood out were 201934B017, 201934B009, 201934B004 and 201934B018 showing productive potential and great aptitude for biomass production.